Archival science in the face of the global challenges linked to sustainability, value and territory. - Medrano Corrales, Isabel; Merino Flecha, Eva; Hernández Olivera, Luis M. (Tábula, 2024)
The adaptation of our profession to this situation is based on our awareness of the changes and needs that occur in the environment in which we carry out our work. This issue of Tábula addresses the opportunities facing Archives, in a context of technological transformation, taking into account the importance of efficient and sustainable management of resources and the challenges posed by territorial diversity. In this way, the content has been developed around three thematic axes: Sustainability, value and territory.